Surgical cure of clarithromycin resistant Mycobacterium chelonae breast implant infection: A case report and review of the literature. (December 2020) - Jhaveri, Vimal V.; Singhal, Dhruv; Riedel, Stefan; Rowley, Christopher F.; Nathavitharana, Ruvandhi R.
Highlights: Reports from Dominican Republic of post breast augmentation NTM infection are common. However, macrolide resistant M. Chelonae in healthy hosts is exceedingly rare. In this case, pregnancy and multiple other factors delayed antibiotics after removal. This is the first confirmed case where the patient was cured with explantation only. Debridement and antimycobacterial therapy remain the standard of care. Abstract: Clusters of patients who obtain cosmetic surgeries abroad have developed surgical site infections due to rapid growing non-tuberculous mycobacteria (NTM). These are usually treated with a combination of surgery and months of anti-mycobacterial therapy, but poor outcomes, including permanent scarring are common. We present a case of a 36-year-old female who developed a clarithromycin-resistant M. chelonae (CRMC) infection after undergoing breast augmentation in the Dominican Republic. She underwent debridement and explant of her silicone implants, but due to a series of complications including discordant antimicrobial susceptibility testing profiles, GI side effects, and then pregnancy, she was unable to receive typical multidrug anti-mycobacterial therapy after surgery. She received close clinical follow up and demonstrated full recovery without any evidence of recurrence of infection at 9 months of follow up. We searched the literature for cases of NTM surgical site infection after breast surgery. To our knowledge, this is the first case report of confirmed NTM breast implant infection being cured with surgery alone, and only the second report of clarithromycin resistant M. chelonae in a patient without disseminated infection or pre-exposure to macrolides. The increasing prevalence of drug resistant NTM infections is an emerging concern for clinicians treating patients with complications related to medical tourism.